Differential Effects of Reperfusion on Cardiac Mitochondrial Subpopulations in a Preclinical Porcine Model of Acute Myocardial Infarction - Chandra Shekar, Kadambari; Yannopoulos, Demetris; Kosmopoulos, Marinos; Riess, Matthias L. (Frontiers in Cell and Developmental Biology, 2022)
Acute myocardial infarction (AMI) leads to localized cardiac ischemia and can be fatal if untreated. Despite being treatable, the threat of ischemia-reperfusion (IR) injury remains high. Mitochondria are central to both propagation and mitigation of IR injury, and cardiac mitochondria are categorized into two major subtypes—subsarcolemmal and interfibrillar mitochondria (SSM and IFM, respectively). We hypothesized that, in our pre-clinical porcine model of AMI, SSM and IFM are differentially affected by reperfusion. AMI was induced in female pigs by balloon occlusion of the left anterior descending artery for 45 min, followed by 4 h of reperfusion. At the end of reperfusion, animals were euthanized. Cardiac SSM and IFM from the affected ischemic area and a nearby non-ischemic area were isolated to compare mitochondrial function using substrates targeting mitochondrial electron transport chain complexes I and II. Despite detecting overall significant differences in mitochondrial function including yield, mitochondrial S3 and S4 respirations, and calcium retention, consistent individual functional differences in the two mitochondrial subpopulations were not observed, both between the two mitochondrial subtypes, as well as between the ischemic and non-ischemic tissue. Nonetheless, this study describes the mitochondrial subtype response within the initial few hours of reperfusion in a clinically relevant model of AMI, which provides valuable information needed to develop novel mitochondrially targeted therapies for AMI.